Networked urbanism social capital in the city - Blokland, Talja 1971-; Savage, Michael 1959- (Ashgate Pub., 2008)
The concept of social capital has gone from being an interesting idea at the turn of the 21st century to being a policy 'doxa' a decade later. Any supposed 'lack' of social capital is now a matter for concern, requiring research and appropriate policy intervention. This book argues that the city poses a major challenge to this agenda.
Keywords: Sociology, Urban; Social capital (Sociology); Communities; Neighborhood; Social integration; Soziales Netzwerk; Stadtentwicklung; Soziales Kapital; Stadtleben; Aufsatzsammlung